EFFECTIVENESS OF SLOW-MATION PACKAGE AND POWERPOINT PRESENTATION ON ACHIEVEMENT OF PRIMARY SCHOOL PUPILS HEALTH EDUCATION - Ibrahim Ologele (Indonesian Journal of Elementary Teachers Education, 2023)
The traditional method of teaching and learning dominate the method of learning that is prominent in Nigeria. The uses of technology for educational system enhance effective teaching learning activity. Therefore, the study investigates the effectiveness of slow-mation package and power point presentation on achievement of primary school pupils Health Education. A quasi-experimental of pre-test, post-test and control single groups design was used for the research. Sixty pupils from the two selected schools formed the sample for the study. The pupils assigned to both and were later tested with Ceramics Achievement Test for data collection. Mean and standard deviation used to test the research questions while t-test analysis used for the formulated hypotheses. A quasi-experimental design was used to determine differences in academic performance of male and female pupils as well as those in private and public school taught with slow-mation package and those taught with power point presentation. The results of the findings indicated that there was no significant difference between male and female students, there was no significant difference between private and public pupils taught with slow-mation package and those taught with power point presentation. As a result of the research, it was recommended that the State Ministry of Education should organise training for primary school teachers on the use of slow-motion and power point presentations which facilitate effective teaching and learning activity. Â Â Â